Combination therapy with oral treprostinil for pulmonary arterial hypertension: a double-blind placebo-controlled clinical trial - White, R. James; Grünig, Ekkehard (American journal of respiratory and critical care medicine, 2020)
Rationale: Oral treprostinil improves exercise capacity in patients with pulmonary arterial hypertension (PAH), but the effect on clinical outcomes was unknown.Objectives: To evaluate the effect of oral treprostinil compared with placebo on time to first adjudicated clinical worsening event in participants with PAH who recently began approved oral monotherapy.Methods: In this event-driven, double-blind study, we randomly allocated 690 participants (1:1 ratio) with PAH to receive placebo or oral treprostinil extended-release tablets three times daily. Eligible participants were using approved oral monotherapy for over 30 days before randomization and had a 6-minute-walk distance 150 m or greater. The primary endpoint was the time to first adjudicated clinical worsening event: death; hospitalization due to worsening PAH; initiation of inhaled or parenteral prostacyclin therapy; disease progression; or unsatisfactory long-term clinical response.Measurements and Main Results: Clinical worsening occurred in 26% of the oral treprostinil group compared with 36% of placebo participants (hazard ratio, 0.74; 95% confidence interval, 0.56-0.97; P = 0.028). Key measures of disease status, including functional class, Borg dyspnea score, and N-terminal pro-brain natriuretic peptide, all favored oral treprostinil treatment at Week 24 and beyond. A noninvasive risk stratification analysis demonstrated that oral treprostinil-assigned participants had a substantially higher mortality risk at baseline but achieved a lower risk profile from Study Weeks 12-60. The most common adverse events in the oral treprostinil group were headache, diarrhea, flushing, nausea, and vomiting.Conclusions: In participants with PAH, addition of oral treprostinil to approved oral monotherapy reduced the risk of clinical worsening.Clinical trial registered with www.clinicaltrials.gov (NCT01560624).
Gesehen am 16.04.2020